The Role of Land Deed Officials (PPAT) In Ensuring Legal Certainty of Land Rights Transfer. Normative Analysis of Supreme Court Decision Number 596 PK/PDT/2020 - Travelina, Khalilla Nada; Handayani, Sri Wahyu (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Land Deed Official (Pejabat Pembuat Akta Tanah/PPAT) is a public official authorized to issue authentic deeds concerning specific legal actions, such as buying and selling and granting, which are crucial in guaranteeing legal certainty of land rights transfer in Indonesia. This research aims to analyze and evaluate the role of the PPAT in achieving legal certainty through a case study of the Supreme Court's Judicial Review (Peninjauan Kembali/PK) Decision No. 596 PK/Pdt/2020, which addresses a dual ownership dispute over land in West Jakarta. The research method used is normative juridical, involving the study of laws and regulations related to the PPAT and legal certainty, as well as an analysis of the judges' legal considerations in the decision. The results of the analysis indicate that this decision affirms the failure of the PPAT's role in performing its due diligence function. The Deed of Engagement to Sell and Buy (APJB) and the Deed of Sale and Purchase (AJB) created by the PPAT were declared invalid and without binding legal force, as they were based on a flawed process and involved a buyer who was deemed not a party acting in good faith. Consequently, the Right to Build (HGB) Certificate issued based on the deed was also revoked, and the rights of the legitimate owner were restored. The conclusion of this study is that the authentic deed created by the PPAT does not provide an absolute guarantee of legal certainty if the deed creation process violates legal provisions or disregards the principle of prudence. The PPAT bears legal and administrative responsibility for losses incurred due to their negligence, thus necessitating a tightening of standard procedures to ensure valid rights for the realization of legal certainty and protection for the public.